(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
Reflecting on the characteristics that saturate the subjects of our time, this article seeks to question authenticity and happiness as cultural imperatives. It seeks as well to perceive its connection with cultural practices and its consequences in the process of producing contemporary subjectivities, considering how these ideals can be perceived in the logic of spectacularization. Therefore, this article briefly goes through the economic, socio-cultural and political processes that were the foundation of contemporary subjectivity. Then, it seeks to define the concepts of happiness and authenticity, establishing, along this path, why and how they constitute social obligations. Finally, the spectacularization of life is argued as a consequence of those cultural imperatives and the way in which they are conducted in postmodern western societies.